PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK DENGAN TEKHNIK AUDIOVISUAL DI RUMAH YATIM TEGAL - Uswatun Insani; Evi Supriatun (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The Prevention of Sexual Harassment as the theme of Health Education can refine children's knowledge about the effort to prevent the violence. Especially for the environment of Tegal City Orphanage. The amount of children of Tegal City Orphanage is about 12 with their own foster parents. The difference between their ages could increase the possibility of sexual harassment. Sexual Harassment between children may happen but also it can happen between the Foster Parents and the child. Therefore the Education of Preventing The Sexual Violence should be enforceable for the students and children of Tegal City Orphanage